2017
DOI: 10.1001/jama.2017.7219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Robotic-Assisted vs Conventional Laparoscopic Surgery on Risk of Conversion to Open Laparotomy Among Patients Undergoing Resection for Rectal Cancer

Abstract: isrctn.org Identifier: ISRCTN80500123.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

69
857
21
21

Year Published

2017
2017
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,033 publications
(1,042 citation statements)
references
References 31 publications
69
857
21
21
Order By: Relevance
“…By further restricting the available space in the already narrow pelvis, robotic platforms seem ideally suited for this group of patients. This is supported by the initial results of the ROLARR trial (NCT01196000), a large randomised control trial comparing robotic to laparoscopic rectal surgery [34, 35]. Data from this trial was presented at the ASCRS and EAES conferences in June 2015, where conversion rates were lower in the robotic cohort in obese patients [36].…”
Section: Discussionmentioning
confidence: 90%
“…By further restricting the available space in the already narrow pelvis, robotic platforms seem ideally suited for this group of patients. This is supported by the initial results of the ROLARR trial (NCT01196000), a large randomised control trial comparing robotic to laparoscopic rectal surgery [34, 35]. Data from this trial was presented at the ASCRS and EAES conferences in June 2015, where conversion rates were lower in the robotic cohort in obese patients [36].…”
Section: Discussionmentioning
confidence: 90%
“…This international multicenter prospective RCT randomized 471 patients from 29 centers in 10 countries to robotic versus laparoscopic resections for rectal cancer 66. The primary outcome was the conversion rate, and the secondary outcomes included 30 day morbidity and mortality, CRM positivity, three year local recurrence rate, disease-free and overall survival rates, and sexual and urinary complications.…”
Section: Types Of Robotic Modelsmentioning
confidence: 99%
“…The robotic surgery helps reduce hospital stay and conversion rates and similar oncological outcomes in TME [17][18][19] . But recently, ROLARR (RObotic vs. LAparoscopic Resection for Rectal Cancer) trial revealed that robotic-assisted laparoscopic surgery do not confer an advantage over laparoscopic surgery in rectal cancer resection for TME [20] . However this trial did not address the e-TME/b-TME.…”
Section: Introductionmentioning
confidence: 99%